Chronic meningoencephalitis with mixed pathology mimics progressive supranuclear palsy. Issue 1 (28th November 2018) - Dale, Marian L; Erten-Lyons, Deniz; Bittner, Frank; Woltjer, Randy
Abstract : We report a case of a progressive supranuclear palsy-like phenotype with rapidly progressive dementia and prominent language and executive dysfunction. Pathological examination revealed no midbrain or white matter tauopathy, but rather chronic meningoencephalitis and other mixed pathology. The cerebrospinal fluid (CSF) in this case showed a novel antibody against central nervous system and renal tissue.